Synergistic Effects of Unintended Pregnancy and Young Motherhood on Shaking and Smothering of Infants among Caregivers in Nagoya City, Japan - Isumi, Aya; Fujiwara, Takeo (Frontiers in Public Health, 2017)
Background Shaking and smothering in response to infant crying are forms of child abuse that often result in death. Unintended pregnancy and young motherhood are risk factors of such child maltreatment that are often comorbid, few studies have examined their synergistic effect on shaking and smothering of infants. We examined the synergistic effects of unintended pregnancy and young motherhood on shaking and smothering among caregivers of infants in Japan. Methods In this retrospective cohort study, a questionnaire was administered to caregivers enrolled for a health check for 3- to 4-month-old infants between October 2013 and February 2014 in Nagoya City, Japan. The questionnaire data were linked to those from pregnancy notification forms registered at municipalities and included information on women’s age and feelings about their pregnancy (N = 4,159). Data were analyzed using logistic regression analysis in 2016. Results Shaking and smothering of 3- to 4-month-old infants occurred at least once in the past month in 2.0 and 1.5% of cases, respectively. Of all participants, 24.8% reported unintended pregnancy while 7.3% were younger than 25 years old. Infants of young mothers (under 25 years old) with unintended pregnancy were 2.77 [95% confidence interval (CI): 1.15–6.68] and 5.61 (95% CI: 2.40–13.1) times more likely to be shaken and smothered, respectively, than those of older mothers with intended pregnancy. In addition, the odds ratio of young mothers with unintended pregnancy regarding smothering was significantly higher than that of older mothers with unintended pregnancy (odds ratio: 2.12; p = 0.02). Conclusion Our findings suggest a synergistic effect of unintended pregnancy and young motherhood on smothering. Infants of young mothers with unintended pregnancy are at greater risk of abuse, especially smothering. Prevention strategies are required for young women with unintended pregnancies.